The Influence of Social Media Users on Purchasing Decisions on UKM in Pontianak - Alfikri, Rahmat; Wardana, Dwiyadi Surya (Lembaga Penelitian dan Pengabdian kepada Masyarkat-Universitas Terbuka, 2021)
There are 57% of the 100 instragram social media users who are used as respondents, with the method of retrieving Accidental Simple Random Sampling, the data obtained is processed using Structural Equation Modeling (SEM) through the IBM Amos v26 program. The purpose of this study is to analyze the extent to which social media users influence purchase decisions. Findings. It is derived from the marketing dimension that Online Communities, Interaction, and Sharing of Content have no positive effect on Social Media, but Accessibility and Credibility have a positive effect on Social Media. Social Media has an influence on Purchasing Decisions, and social media cannot be said to be an intervening variable that affects the relationship between independent variables and dependent variables into indirect and un observable and measurable relationships.